KEPEMIMPINAN, KOMPENSASI, DAN MOTIVASI SERTA PENGARUHNYA TERHADAP KEPUASAN KERJA - Raden Rudi Alhempi (Universitas Trisakti, 2012)
Employee job satisfaction is an important target in human resource management, because it is directly or indirectly affects the productivity of labor. Job satisfaction can be made if the variables that influence it, including work motivation, leadership and leadership can be properly applied and accepted by all employees within an organization.This study aimed to determine the effect of leadership, compensation and motivation on job satisfaction of employees at PT. XYZ. The number of samples used is 188 employees. Data were analyzed through structural equation models. Although the model is estimated less fit but estimation results show that leadership, compensation, and motivation have a positive and significant influence on job satisfaction of employees. Motivation is a variable that has the highest effect on job satisfaction of employees.Keywords: Leadership, Compensation, Motivation, Job satisfaction